Bosnia and Herzegovina : Technical Assistance Report-Report on Government Finance Statistics Technical Assistance Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This technical assistance report (TA) report specifies mission's efforts to support the Bosnia and Herzegovina authorities, with a specific focus on the Republic of Srpska (RS), in improving government finance statistics (GFS) for decision making. This mission's focus has been to continue developing reconciliation processes, to develop a compilation process for nonbudgetary public sector units, and to discuss classification questions in context of GFS compilation per the European System of National and Regional Accounts 2010 and the Government Finance Statistics Manual 2014. This mission initiated the development of a standardized compilation procedure for nonbudgetary public sector units, and, more specifically extra-budgetary units. The August 2017 mission mapped out flows between the budget, the health fund, the health institutions, and patients (household), concerning the provision of health care and its funding. This mapping is expected to help serve the classification of functional expenditure of the health fund and the health care providers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet